2008
DOI: 10.1021/ct8001738
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Density Functional Theory/Multireference Configuration Interaction Method on Electronic Excitation of Extended π-Systems

Abstract: The combined density functional theory/multireference configuration interaction (DFT/MRCI) method [Grimme and Waletzke. J. Chem. Phys. 1999, 111, 5645] has been employed to study the 1 L a and 1 L b states of linear polyacenes and the low-lying triplet and singlet states of linear polyenes and diphenyl-polyenes. We have systematically investigated the dependence of the electronic state properties on technical parameters of the calculations such as the atomic orbital basis set or the geometry optimization appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
201
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(227 citation statements)
references
References 93 publications
23
201
2
1
Order By: Relevance
“…46 According to these results the 1B − u state becomes the S 2 state for N 22 at the chosen Franck-Condon geometry, while the 3A − g singlet excitation stays above the 1B + u state in all polyenes considered. In summary, the quoted calculations 26,[43][44][45] and, here, particularly Refs. 43 and 45, essentially confirmed the early PPP/MRCI descriptions of the low-lying electronically excited singlet states concerning the relative spacings of the covalent and ionic states in the polyenes.…”
Section: Quantum Chemical Descriptions Of Polyene Spectramentioning
confidence: 69%
See 3 more Smart Citations
“…46 According to these results the 1B − u state becomes the S 2 state for N 22 at the chosen Franck-Condon geometry, while the 3A − g singlet excitation stays above the 1B + u state in all polyenes considered. In summary, the quoted calculations 26,[43][44][45] and, here, particularly Refs. 43 and 45, essentially confirmed the early PPP/MRCI descriptions of the low-lying electronically excited singlet states concerning the relative spacings of the covalent and ionic states in the polyenes.…”
Section: Quantum Chemical Descriptions Of Polyene Spectramentioning
confidence: 69%
“…26,[43][44][45] For instance, in 2004 Kurashige et al 43 studied the alltrans-polyenes with 6 ≤ N ≤ 28π -electrons in a correlated ab initio setting, which restricted the active space for full CI expansions to the five highest occupied and five lowest unoccupied molecular orbitals (MOs), and estimated σ -π interactions by second order perturbation theory. According to these calculations the vertical transition to the 1B − u state appears below the 1B + u transition at N ≥ 14 and the transition to the 3A − g state at N ≥ 22.…”
Section: Quantum Chemical Descriptions Of Polyene Spectramentioning
confidence: 99%
See 2 more Smart Citations
“…15 They ascribed the ordering anomaly to the electron correlation effects. Since then, there have been continuous and considerable investigations, such as by Tavan and Schulten, 16 Cave and Davidson, 17 Nakayama et al, 18 Hsu et al, 19 Serrano-Andres et al, 20 Starcke et al, 21 Marion and Gilka, 22 Shahi et al, 23 in calculating the 2A g /1B u orderings for the short unsubstituted polyene and Shukla 24 for the substituted polyene [poly(diphenylacetylene)]. It is found that the 2A g state has important contributions from electron double excitation configuration in the molecular orbital picture.…”
Section: Introductionmentioning
confidence: 99%